The Correlation Between the Definition of Profit and Age - Siti Hauliyatul Izzah; M. Ali Fikri (PT FORMOSA CENDEKIA GLOBAL, 2024)
The objective of this study is to determine if there is a correlation between the concept of profit and an individual's age. This research is conducted utilizing quantitative methodologies and using associative techniques. The data analysis technique employed is eta correlation. A questionnaire was employed as the study instrument, with a sample size of 98 individuals. The research findings indicate a strong correlation between the concept of profit and age, particularly in the sufficient category. The majority of respondents in the 20-50 age range associated profit with monetary gain, while in the 60-70 age range, the focus shifted towards health as the primary meaning of profit. This research demonstrates that the concept of profit encompasses not only tangible aspects, but also intangible aspects such as education and health.